Characteristics of changes in fetal doppler blood flow parameters in women with gestational hypertension at different stages of pregnancy - Vol. V. Podolskyi; V.V. Podolskyi; V.M. Znak (Репродуктивная эндокринология, 2023)
Research objectives: to determine the resistance index, pulsatile index and systolic-diastolic ratio in the fetal middle cerebral artery, fetal aorta and umbilical artery in women with gestational hypertension (GH). Materials and methods. The main group included 50 pregnant women with GH, the control group included 50 healthy pregnant women. Blood pressure level and ultrasound dopplerometric indicators of fetal blood flow were determined at the 20th, 25th, 30th, 35th, and 40th weeks of pregnancy. Results. Changes in Doppler blood flow indicators in the umbilical artery in women of the main group were observed earlier than changes in these indicators in the fetal aorta, namely from the 30th week of pregnancy: the resistance index was 0.46 ± 0.08, the pulsatility index was 0.8 ± 0.23, the systolic-diastolic ratio was 2 ± 0.19, and in women of the control group these indicators were 0.69 ± 0.17, 1.46 ± 0.21 and 3 ± 0.33, respectively. At the 35th week of pregnancy, the trend towards a decrease in dopplerometric indicators of blood flow in the umbilical artery in women of the main group continued, the value of these indicators was: resistance index – 0.42 ± 0.09, pulsatility index – 0.68 ± 0.23, systolic diastolic ratio – 1.8 ± 0.16, and in women of the control group these indicators were 0.68 ± 0.13, 1.43 ± 0.11 and 2.94 ± 0.24, respectively. The lowest Doppler parameters of blood flow in the umbilical artery in women of the main group were at 40th week: resistance index – 0.37 ± 0.07, pulsatility index – 0.63 ± 0.21, systolic-diastolic ratio – 1.6 ± 0.13, and in women of the control group these indicators were 0.67 ± 0.11, 1.4 ± 0.1, and 2.87 ± 0.21, respectively. Conclusions. Blood flow indicators in the aorta and umbilical arteries, as well as in the middle cerebral artery of the fetus in women with GH differ from such indicators in healthy women. Decreased blood flow may indicate a risk of hypoxia and neurological problems for fetus. Therefore, it is important to diagnose GH in time and monitor fetal blood flow indicators using ultrasound to prevent possible complications and preserve the fetus and mother health.